Index of Non-tariff Measures: A Study of the EU Textile and Garment Market. Issue 3 (August 2019) - Chattopadhyay, Sudeshna
The post-WTO period has witnessed a rapid increase in growth of non-tariff measures (NTMs). As a result, quantification of NTMs has emerged as an important policy question. Quantification of NTMs is often challenging as these measures, in most cases, do not have direct numerical measurements. Hence, proxies have to be constructed. The present article proposes a methodology which uses time series information on legislation related to NTMs to construct comprehensive indices of NTMs. The incidence of NTMs is very high in the textile and garments (T&G) sector in the EU, which is also an important destination of India's textile and garments exports. Hence, the EU textile and garments sector is selected as a case study. Separate NTM indices are constructed for the German and rest of the EU market, and the effects of these indices on the flow of India's T&G exports are explored. JEL Codes: F13, F18